Penerapan Konsep Rasi Bintang Polaris pada Redesain Terminal Pelabuhan Penyebrangan Mentigi: Bahasa Indonesia - Kesha Gde Adibhakta Kirana; Ni Wayan Nurwarsih; Agus Kurniawan; Gde Bagus Andhika Wicaksana; Made Arya Adiartha (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Nusa Penida is a small island located southeast of Bali and is part of Klungkung Regency. The natural beauty of Nusa Penida is the main attraction for tourists. Although Nusa Penida has great tourism potential, transportation access to Nusa Penida is one of the challenges. Such as the lack of supporting facilities at the Port Terminal, which is relatively small in size while Nusa Penida experiences rapid growth in the number of tourists from year to year. One of them is the condition of Mentigi Port Terminal, where the infrastructure is poorly maintained and inadequate, making it inefficient to handle the increasing number of tourist ships and passengers, thus potentially hindering economic and tourism growth. Observation is the use of a method by observing and recording data on analyzed matters to enhance insight. Data collection through two-way communication (interviews) to gather information from relevant respondents where the interviewer directly asks questions about a researched object and previously designed data collection for research data collection. Literature Study is a study by collecting and recording data sourced from literature, journals, documents, etc., to obtain researched data. Currently, there is no suitable transportation center for tourists on Nusa Penida, especially the port in terms of facilities that do not follow current developments as a transportation hub on Nusa Penida Island. Therefore, Redesign of Mentigi Port Terminal are crucial because from year to year, tourists are very active and increasing in visiting Nusa Penida, so it is necessary to have a terminal and supporting facilities at the port to facilitate the increasing number of tourists so that they feel safe and comfortable in their first impression stepping foot on Nusa Penida.